Some aspects and features of tourism management in Macedonia - Konstantin Petkovski; Ace Milenkovski; Mijalce Gjorgievski (UTMS Journal of Economics, 2015)
The importance of human recourse\~n management is important in every field of work and in every enterprise, especially in enterprises operating in the tourism sector. We underline this because the tourism commercial sector is mainly based and depends on qualified human potentialwhich will be correctly managed. The same applies to the question of the human resources management in Republic of Macedonia. The employees in tourism field have to be enabled and qualified to fulfil all future requests and standards connected with their working performances. The specificity of our companies included in the tourist sector is the fact that there are small companies operating according to the number of employees; in such cases, the managers commonly do not perform only the leadership function only, but in most cases there is an overlapping with the executive function. For these reasons, it is hard to discuss a classical type of management because, as we mentioned, the Macedonian companies compared to those from more developed countries, are different in their size, and therefore in their style of management.
Keywords: M00; 330; management; human resources; tourism; education; leadership